A layered diamond and a method for preparing the same
The layered diamonds synthesized by the static pressure method solve the problems of single crystal diamond and poly crystal diamond blade, low grinding efficiency and short life, and achieve higher cutting efficiency and longer service life, and safely reliable.
Patent Information
- Application Number
- CN202411389006.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-08
AI Technical Summary
In the prior art, single crystal diamond and polycrystalline diamond have fewer edges, low grinding efficiency and shorter life.
The layered diamonds synthesized by static pressure method, through specific raw materials ratio and process treatment, form diamonds with layered structure and efficient cutting performance.
Improved the cutting efficiency and service life of diamonds, solved the problem of low blade mouth and low grinding efficiency, and produced through static pressure to avoid the problem of narrow safety risks and narrow grain range of explosion method.
Smart Images

Figure CN118929658B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diamond production and processing, in particular to a layered diamond and a preparation method thereof. Background Art
[0002] Diamond is a mineral composed of carbon and is an allotrope of carbon. Diamond is the hardest substance that exists naturally in nature and can be divided into detonation nanodiamond, single crystal diamond and polycrystalline diamond. Detonation nanodiamond production enterprises are represented by Beijing Guoruisheng Technology Co., Ltd., and the diamonds they produce are mainly used in the polishing field. Among the single crystal diamond production enterprises, Zhongnan Diamond and Huanghe Cyclone are the representatives, and the diamonds they produce are mainly used in the stone and construction industries. China's single crystal diamond production accounts for more than 90% of the world. Polycrystalline diamond production enterprises are represented by Henan Feimeng Diamond Co., Ltd. and Zhengzhou Ward Superhard Materials Co., Ltd., and the polycrystalline diamonds they produce are mainly used for resin diamond grinding wheels.
[0003] The surface of single crystal diamond is smooth, but the holding force is poor, it is easy to fall off, and it is not sharp enough. Polycrystalline diamond has an uneven surface, good holding force, and is suitable for resin bond grinding wheels. The interior is a single crystal block structure. The grinding efficiency of polycrystalline diamond is more than 3 times that of single crystal diamond. The scratches and micro cracks on the grinding surface are small, and the finish is high. It is widely used in high-tech fields such as electronics, aerospace, and aviation. Polycrystalline nanodiamonds produced by the explosion method are a new type of grinding material. It has irreplaceable advantages in sapphire grinding and other aspects. However, the structure of polycrystalline diamonds produced by the explosion method is an irregular granular structure, the surface is uneven, there are fewer grinding edges, the grinding efficiency is low, and the life is short.
[0004] In addition, in terms of production methods, the domestic static pressure method for producing diamonds is basically based on single crystal diamonds. The existing polycrystalline diamonds are produced by the high temperature and high pressure generated by the instantaneous explosion to achieve the transformation of graphite into diamond. However, the polycrystalline diamonds produced by the explosion method have the following problems: 1) The particle size is too fine, below 20 microns, and can only be used for polishing, with a narrow range of use; 2) The polycrystalline diamonds produced by the explosion method have fine particles and are not easy to clean, and have a high impurity content; 3) The production by the explosion method involves issues such as explosive safety and explosive control, and is not suitable for large-scale production. Summary of the invention
[0005] The first purpose of the present invention is to overcome the shortcomings of the prior art and provide a layered diamond to solve the problems of single crystal diamond and polycrystalline diamond in the prior art, such as few cutting edges, low grinding efficiency and short life; the layered diamond has the advantages of higher grinding efficiency and longer service life.
[0006] The second purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing layered diamond to solve the problem of few grinding edges of single crystal diamond in the prior art and the problem of poor cold impact toughness (TI) and thermal impact toughness (TTI) of existing polycrystalline diamond. The obtained layered diamond has the advantages of higher cutting efficiency and longer service life.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The layered diamond of the present invention is a diamond with a layered structure; when the surface morphology of the layered diamond is observed in any direction, the layered diamond is a tetradecahedron or an octahedron; when the surface morphology of the layered diamond crushing surface is observed in any direction, the layered diamond crushing surface is a layered polycrystalline diamond structure.
[0009] Furthermore, the particle size of the layered diamond is between 20 and 2500 microns.
[0010] In this specification, unless otherwise specified, the percentages are percentages by mass.
[0011] Furthermore, the layered diamond is mainly prepared from the following raw materials in percentage by weight: 30%-60% catalyst, 30%-60% graphite, 1%-10% No. 1 additive masterbatch, 1%-10% No. 2 additive masterbatch, and the sum of the weight percentages of each raw material is 100%.
[0012] The catalyst is a catalyst, which is a nickel-iron alloy powder, including 20-40% by mass of nickel and 60-80% by mass of iron (preferably 30% by mass of nickel and 70% by mass of iron, hereinafter referred to as catalyst).
[0013] The No. 1 additive masterbatch is mainly composed of the following raw materials in percentage by weight: 50-90% graphite, 10%-50% diamond powder, 0.5%-15% metal aluminum powder, 0.5%-15% metal titanium powder, and 0.5%-15% amorphous boron powder, and the sum of the weight percentages of each raw material is 100%.
[0014] Furthermore, the diamond powder in the No. 1 additive mother powder is diamond powder produced by diamond of type II or higher quality, and the diamond powder D50 is 4-9.5 microns.
[0015] Furthermore, the diamond powder in the No. 1 additive mother powder is produced from Type II or higher quality diamonds, and the diamond powder D50 is one of 4-5 microns, 5-6 microns, 6-7 microns, 7-8 microns, and 8-9 microns.
[0016] Furthermore, the diamond powder in the No. 1 additive mother powder is produced from Type II or higher quality diamonds. The present invention uses the diamond powder produced from Type II or higher quality diamonds as a seed for layered diamond growth. Because the impurity content of diamond powders lower than Type II is high, the particle size distribution of the grown layered diamond is not concentrated and the grade is low.
[0017] Furthermore, the diamond powder in the No. 1 additive mother powder is produced by diamond of type II or higher quality, and the diamond powder D50 is one of 4-5 microns, 5-6 microns, 6-7 microns, 7-8 microns, and 8-9 microns. The original particle size of the seed crystal for diamond growth is closely related to its content in graphite. Generally speaking, the larger the particle size of the diamond seed crystal and the smaller the number, the finer the diamond particles grown. In the present invention, 8-9 micron diamond seeds are used to grow 25 / 30 (using 25 mesh and 30 mesh standard sieves produced by Bashan Aviation 540 Factory, passing 25 mesh but not passing 30 mesh), 30 / 35 (using 30 mesh and 35 mesh standard sieves produced by Bashan Aviation 540 Factory, passing 25 mesh but not passing 30 mesh, similar to the following), 35 / 40, 40 / 45 diamonds, except that the concentration of diamond seeds in graphite is getting higher and higher; 6-7 micron diamond seeds are used to grow 50 / 60, 60 / 70, 70 / 80 diamond, but the concentration of diamond seeds in graphite is getting higher and higher; 5-6 micron diamond seeds are used to grow 80 / 100, 100 / 120, 120 / 140 diamond, but the concentration of diamond seeds in graphite is getting higher and higher; 4-5 micron diamond seeds are used to grow 140 / 170, 170 / 200, 200 / 230, 230 / 270, 270 / 325, 325 / 400, 400 / 500 diamond, but the concentration of diamond seeds in graphite is getting higher and higher.
[0018] Particularly preferably, the diamond powder in the No. 1 additive mother powder is a layered diamond powder produced from layered diamond with a Ti value (indicating the rigidity and strength of the material) greater than 70 as raw material, and the diamond powder D50 is one of 4-5 microns, 5-6 microns, 6-7 microns, 7-8 microns, and 8-9 microns.
[0019] Furthermore, the mass purity of the metal aluminum powder in the No. 1 additive mother powder is greater than or equal to 99.99%, and the D50 of the metal aluminum powder is 10-20 microns.
[0020] Furthermore, the mass purity of the metal aluminum powder in the No. 1 additive mother powder is greater than or equal to 99.99%. The present invention uses a metal aluminum powder with a mass purity greater than 99.99% for layered diamond synthesis. Because the low-purity metal aluminum powder has a high impurity content, it will affect the purity of the grown layered diamond, resulting in a low grade of the layered diamond.
[0021] Further, the metal aluminum powder D50 in the No. 1 additive mother powder is 10-20 microns. The present invention uses a metal aluminum powder D50 of 10-20 microns. It is used for layered diamond synthesis. Because the metal aluminum powder particle size is too large, the metal aluminum powder is unevenly dispersed, which will affect the purity of the grown layered diamond, resulting in a low grade of the layered diamond. Because the metal aluminum powder particle size is too small, the metal aluminum powder is easily oxidized when dispersed, which will affect the purity of the grown layered diamond, resulting in a low grade of the layered diamond.
[0022] Furthermore, the mass purity of the metal titanium powder in the No. 1 additive mother powder is greater than 99.9%, and the D50 of the metal titanium powder is 10-20 microns.
[0023] Furthermore, the purity of the metal titanium powder in the No. 1 additive master powder is greater than 99.9%. The present invention uses a metal titanium powder with a purity greater than 99.99% for layered diamond synthesis. Because the low-purity metal titanium powder has a high impurity content, it will affect the purity of the grown layered diamond, resulting in a low grade of the layered diamond.
[0024] Furthermore, the D50 of the metal titanium powder in the No. 1 additive mother powder is 10-20 microns. The present invention uses a metal titanium powder D50 of 10-20 microns. It is used for layered diamond synthesis. Because the particle size of the metal titanium powder is too large, the metal titanium powder is unevenly distributed, which will affect the purity of the grown layered diamond, resulting in a low grade of the layered diamond. Because the particle size of the metal titanium powder is too small, the metal titanium powder is easily oxidized when dispersed, which will affect the purity of the grown layered diamond, resulting in a low grade of the layered diamond.
[0025] Furthermore, the mass purity of the amorphous boron powder in the No. 1 additive masterbatch is greater than 99%, and the D50 of the amorphous boron powder is 0.1-10 microns.
[0026] Furthermore, the mass purity of the amorphous boron powder in the No. 1 additive mother powder is greater than 99%. The present invention uses amorphous boron powder with a mass purity greater than 99% for layered diamond synthesis. Because the impurity content of low-purity amorphous boron powder is high, it will affect the purity of the grown layered diamond, resulting in low grade of layered diamond.
[0027] Further, the amorphous boron powder D50 in the No. 1 additive mother powder is 0.1-10 microns. The present invention uses amorphous boron powder D50 of 0.1-10 microns. It is used for layered diamond synthesis. Because the particle size of the metal titanium powder is too large, the metal titanium powder is unevenly distributed, which will affect the purity of the grown layered diamond and result in low grade of the layered diamond.
[0028] The No. 2 additive masterbatch is mainly composed of the following raw materials in percentage by weight: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium nitride, and 0.5%-15% carbon nitride.
[0029] Furthermore, the No. 2 additive master powder is mainly prepared by the following raw materials and processes in weight percentage: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, 1%-30% urea, added into a rotary CVD deposition furnace, and deposited in situ under nitrogen protection to generate lithium nitride and carbon nitride. The synthesized No. 2 additive master powder deposited in situ under nitrogen protection has low oxygen content, which is conducive to improving the grade of layered diamond.
[0030] Alternatively, further, the No. 2 additive master powder is mainly prepared from the following raw materials in weight percentage: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, 1%-30% urea, added to a rotary CVD deposition furnace, and in-situ deposited under the protection of nitrogen and argon (preferably nitrogen and argon volume ratio of 2:1) to generate lithium nitride and carbon nitride. In-situ deposition under the protection of nitrogen and argon, the synthesized No. 2 additive master powder has a low oxygen content, which is conducive to improving the grade of layered diamond.
[0031] Alternatively, further, the No. 2 additive mother powder is mainly prepared from the following raw materials in weight percentage: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, and 1%-30% urea, which is added into a rotary CVD deposition furnace and in situ deposited under the protection of nitrogen and hydrogen (preferably the volume ratio of nitrogen and hydrogen is 2:1) to generate lithium nitride and carbon nitride.
[0032] Particularly preferably, the No. 2 additive master powder is mainly prepared from the following raw materials in weight percentage: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, 1%-30% urea, added to a rotary CVD deposition furnace, and in-situ deposited under the protection of nitrogen and hydrogen (preferably nitrogen and hydrogen in a volume ratio of 2:1) to generate lithium nitride and carbon nitride. The synthesized No. 2 additive master powder is deposited in-situ under the protection of nitrogen and hydrogen, and has a low oxygen content, which is conducive to improving the grade of layered diamond.
[0033] Furthermore, during the preparation of the No. 2 additive master powder, the deposition temperature of the in-situ deposition is 500-750 degrees Celsius. When the temperature is lower than 500 degrees Celsius, the synthesis reaction is incomplete; when the temperature is higher than 750 degrees Celsius, the components of the No. 2 additive master powder are segregated.
[0034] The second object of the present invention is to provide a method for preparing layered diamond, which adopts a static pressure method to manufacture layered diamond to solve the problem of less grinding edges of single crystal diamond in the prior art and the poor cold impact toughness (TI) and thermal impact toughness (TTI) of the existing polycrystalline diamond, and the diamond has the advantages of higher cutting efficiency and longer service life. The layered diamond is used to produce layered polycrystalline diamond powder, which can solve the problems of narrow particle size range, high impurity content and dangerous production process caused by the explosion method in the prior art.
[0035] The method for preparing the layered diamond adopts a static pressure method, in which the raw material is placed in a press device and pressurized and heated for synthesis treatment to obtain the layered diamond.
[0036] Furthermore, the preparation method of the layered diamond is to mix the catalyst, graphite, additive master powder No. 1 and additive master powder No. 2 evenly and press them into a column, assemble them with accessories such as phyllite blocks and steel cups into a synthetic block, place it in a six-sided top press or a two-sided top press, and pressurize and heat the six-sided top press or the two-sided top press to perform synthesis treatment.
[0037] Preferably, the preparation method of the layered diamond is to mix the catalyst, graphite, additive master powder No. 1 and additive master powder No. 2 evenly and press them into a column, assemble them with accessories such as phyllite blocks and steel cups into a synthetic block, place it in a six-sided top press, pressurize and heat the six-sided top press for synthesis treatment, the pressurization pressure of the six-sided top press is 70-85Mpa, and the temperature is 1350-1650℃.
[0038] Furthermore, the method for preparing the layered diamond comprises the following steps:
[0039] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder uniformly and press them into a column. Sinter the column to 1000°C-1200°C (preferably 1100°C) in a nitrogen atmosphere (preferably nitrogen purity is greater than 99.99%), and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0040] S2. Place the synthetic block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 5-7Mpa in 0-3 seconds, then slowly pressurize to 50-55Mpa in 80-100 seconds (preferably 90 seconds), and maintain the pressure for 450-600 seconds; when the pressure increases to 50-55MPa, start heating and temperature rise from room temperature to 1450-1650℃, and keep the temperature;
[0041] S3, after the pressure maintenance at 50-55 MPa in step S2 is completed, the pressure is quickly increased to 60-65 MPa for pressure maintenance, and the pressure maintenance time is 500 seconds to 650 seconds (preferably 620 seconds);
[0042] S4. After the pressure maintenance at 60-65 MPa in step S3 is completed, the temperature is reduced from 1450-1650° C. to 1350-1500° C. and maintained unchanged;
[0043] S5. After the temperature drops to 1350-1500°C, the pressure is further increased to 75-85MPa and maintained for 800 seconds to 1200 seconds (preferably 1200 seconds);
[0044] S6, after the pressure maintenance in step S5 is completed, the temperature begins to decrease, and the pressure is released again when the temperature drops to room temperature, that is, the layered diamond is synthesized.
[0045] Furthermore, in step S2, the pressure is first increased to 5-7 MPa after 1-2 seconds, and then increased to 50-55 MPa at a pressure rate of 0.3-0.8 MPa / s, and the pressure is maintained for 500-550 seconds; when the pressure is increased to 50-55 MPa, heating is started, and the temperature is increased from room temperature to 1450-1650° C. after 10-20 seconds, and the temperature is maintained. The process in this step can effectively reduce the consumption of the top hammer.
[0046] Furthermore, in step S3, after the pressure maintenance at 50-55 MPa is completed, the pressure is rapidly increased to 60-65 MPa after 80-95 seconds, and the pressure is maintained for 500-540 seconds.
[0047] Furthermore, the pressure relief rate during pressure relief in step S6 is 0.5-1 MPa / s.
[0048] Furthermore, the method for preparing the layered diamond comprises the following steps:
[0049] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder uniformly and press them into a column, sinter the column to 1000°C-1200°C (preferably 1100°C) in a nitrogen atmosphere, and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block;
[0050] S2. Place the composite block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 6MPa in 0-1 second, then slowly increase the pressure to 51-53Mpa in 90 seconds, and maintain the pressure for 530-550 seconds; when the pressure increases to 51-53MPa, start heating and temperature rise from room temperature to 1450-1650℃, and keep the temperature;
[0051] S3, after the pressure maintenance at 51-53 MPa in step S2 is completed, the pressure is quickly increased to 62-64 MPa for pressure maintenance;
[0052] S4. After the pressure maintenance at 62-64 MPa in step S3 is completed, the temperature is reduced from 1450-1650° C. to 1350-1500° C. and maintained unchanged;
[0053] S5. After the temperature drops to 1350-1500°C, continue to increase the pressure to 76-80MPa and maintain the pressure;
[0054] S6, after the pressure maintenance in step S5 is completed, the temperature is lowered, and when the temperature drops to room temperature, the pressure is released to synthesize a layered diamond synthetic rod.
[0055] Furthermore, the pressure relief rate during the pressure relief in step S6 is 0.5-0.6 MPa / s.
[0056] The layered diamond obtained by the invention is particularly suitable for being used as a metal binder to produce marble saw blade segments and diamond beads on diamond wire saws.
[0057] Compared with the existing diamond production technology, the present invention has the following beneficial effects:
[0058] 1) The layered diamond has a unique layered structure after cleavage. The edge of the single-piece layered diamond structure is equivalent to the grinding edge. During operation, multiple edges can be provided to cut and grind the material that needs to be ground. Since multiple edges are cut at the same time, the cutting efficiency can be improved, the service life of the diamond can be extended, and the smoothness of the cutting surface can be improved. In addition, the minimum size of the grinding edge of the layered diamond in the present invention is about 20-200 nanometers, so it has a nano-scale cutting edge, and the cutting surface has the advantages of few scratches, few microcracks and high smoothness. At the same time, the layered diamond prepared by the method of the present invention has extremely high brittleness, so it can always maintain a cold grinding state during the grinding process.
[0059] 2) The layered diamond powder prepared by the layered diamond preparation method of the present invention is a nano-layered polycrystalline diamond powder synthesized by static pressure method, which opens up a new path for synthesizing nano-polycrystalline diamond by six-sided top pressure static pressure method and fills the technical gap in the superhard material industry.
[0060] 3) The layered diamond prepared by the method of the present invention has an overall outer shape of a tetradecahedron and a layered internal structure, which is very suitable for cutting and grinding.
[0061] 4) The layered diamond of the present invention is statically pressed by a six-sided top press, and the high voltage generated during production and the high temperature generated by transformer DC heating are used to achieve the transformation of the graphite phase into the diamond phase. During the production process, the particle size can be controlled according to the synthesis time and synthesis process, thereby expanding the application range of the layered diamond.
[0062] Furthermore, the layered diamond of the present invention is statically pressed by a six-sided top press, and the high voltage generated during production and the high temperature generated by direct current heating of the transformer are used to realize the transformation of the graphite phase into the diamond phase. In the production process, the particle size can be controlled according to the synthesis time and synthesis process, and the particle size range is: 18 / 20, 20 / 25, 25 / 30, 30 / 35, 35 / 40, 40 / 45, 45 / 50, 50 / 60, 60 / 70, 70 / 80, 80 / 100, 100 / 120, 120 / 140, 140 / 170, 170 / 200, 200 / 230, 230 / 270, 270 / 325, 325 / 400, 400 / 500, 600 / 800, thereby expanding the application range of the layered diamond.
[0063] The layered diamond produced by the present invention has a layered structure on its crushed cleavage surface, which can solve the problem of less grinding edges of single crystal diamond in the prior art and the problem of poor cold impact toughness (TI) and thermal impact toughness (TTI) of existing polycrystalline diamond. The diamond has the advantages of higher cutting efficiency and longer service life. The layered diamond powder processed by the layered diamond produced by the present invention has a layered nanostructure on its micro-section, which is very suitable for making diamond wire saws, resin polishing pads, and diamond polishing liquids. The formula and preparation method provided by the present invention can produce diamond products with the same particle size as those prepared by the explosion method. The diamond products not only have the characteristics of the diamond morphology of the explosion method, but also have a wider particle size range, thus breaking the bottleneck that the production of nano polycrystalline diamonds in the traditional process can only be produced by the explosion method.
[0064] Compared with the explosion method for producing nanodiamonds, the method provided by the present invention has the following advantages:
[0065] 1) The cost of producing nano polycrystalline diamond by using the static pressure method to synthesize layered diamond is lower than that of synthesizing nano polycrystalline diamond by the explosion method;
[0066] 2) The layered diamond particle size produced by the static pressure method of the present invention is between 20 and 2500 microns, and the coarse and fine particle sizes can be used in the grinding wheel industry, stone industry, 3C industry, sapphire industry, silicon carbide industry, and the application field is relatively wide;
[0067] 3) The layered diamond synthetic rod synthesized by the six-sided top press is firstly subjected to mechanical crushing, chemical electrolysis to remove the catalyst metal, shaking table to remove the excess graphite, pickling, screening and selection to obtain high-purity coarse and fine particle layered diamond; then, air flow crushing, pickling and grading are carried out to obtain high-purity nano-polycrystalline diamond powder.
[0068] 4) The method of the present invention is safer and more reliable, and more suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is an electron microscope image of the layered diamond obtained in Example 1 of the present invention, magnified 100 times;
[0070] Figure 2 This is an electron microscope image magnified 50,000 times of the nano-polycrystalline diamond powder produced after the layered diamond obtained in Example 1 of the present invention is crushed;
[0071] Figure 3 This is an electron microscope image of the cleavage surface of the layered diamond obtained in Example 1 of the present invention after TI impact, magnified 500 times;
[0072] Figure 4 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 1 of the present invention is crushed and magnified 1000 times;
[0073] Figure 5 The figure shows an electron microscope photograph of particles obtained after the layered diamond obtained in Example 1 of the present invention is crushed and magnified 5000 times;
[0074] Figure 6 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 1 of the present invention is crushed and magnified 10,000 times;
[0075] Figure 7 Shown is the XRD pattern of the layered diamond obtained in Example 1 of the present invention;
[0076] Figure 8 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 2 of the present invention is crushed and magnified 1000 times;
[0077] Fig. 9 The figure shows an electron microscope photograph of particles obtained after the layered diamond obtained in Example 2 of the present invention is crushed and magnified 5000 times;
[0078] Fig.10 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 2 of the present invention is crushed and magnified 10,000 times;
[0079] Fig.11 Shown is the XRD pattern of the layered diamond obtained in Example 2 of the present invention;
[0080] Fig.12 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 3 of the present invention is crushed and magnified 1000 times;
[0081] Fig.13 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 3 of the present invention is crushed and magnified 5000 times;
[0082] Fig.14 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 3 of the present invention is crushed and magnified 10,000 times;
[0083] Fig.15 Shown is the XRD pattern of the layered diamond obtained in Example 3 of the present invention;
[0084] Fig.16 The figure shows an electron microscope photograph of particles obtained after the layered diamond obtained in Example 4 of the present invention is crushed and magnified 500 times;
[0085] Fig.17 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 4 of the present invention is crushed and magnified 2000 times;
[0086] Fig.18 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 4 of the present invention is crushed and magnified 5000 times;
[0087] Fig.19 Shown is the XRD pattern of the layered diamond obtained in Example 4 of the present invention;
[0088] Fig. 20 The figure shows an electron microscope photograph of particles obtained after the layered diamond obtained in Example 5 of the present invention is crushed and magnified 500 times;
[0089] Fig.21 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 5 of the present invention is crushed and magnified 2000 times;
[0090] Fig. 22 The figure shows an electron microscope photograph of the particles obtained after the layered diamond obtained in Example 5 of the present invention is crushed and magnified 5000 times;
[0091] Fig.23 Shown is the XRD pattern of the layered diamond obtained in Example 5 of the present invention;
[0092] Fig.24 The figure shows an electron microscope photograph of the agglomerated abrasive with a secondary particle size D50 of 35 μm obtained in Example 8 of the present invention, which is magnified 3000 times;
[0093] Fig.25 The photo of the layered diamond with a primary particle size of 45 / 50 obtained in Example 1 of the present invention under an optical microscope is shown;
[0094] Fig.26 A photograph of the layered diamond with a primary particle size of 40 / 45 obtained by the present invention under an optical microscope. DETAILED DESCRIPTION
[0095] The embodiments of the present invention will be described in detail below with reference to examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0096] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0097] like Figure 1 , Figure 2 and Figure 3 As shown, the present invention provides a layered diamond, which includes single crystal diamond with a single crystal structure and polycrystalline diamond with a nano-layered structure after being crushed. Figure 1 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 1 of the present invention magnified 50 times. Figure 2 This is an electron microscope photograph of the layered polycrystalline diamond obtained after the layered diamond obtained in Example 1 of the present invention is crushed. Figure 3 This is an electron microscope image of the cleavage surface of the layered diamond obtained in Example 1 after TI impact, magnified 5000 times.
[0098] The layered diamond of the present invention is a single crystal diamond with a layered structure; when the surface morphology of the layered diamond is observed in any direction, the layered diamond is a tetradecahedron or an octahedron; when the surface morphology of the layered diamond crushing surface is observed in any direction, the layered diamond crushing surface is a layered polycrystalline diamond structure. The internal structure is a layered structure, which is very suitable for cutting and grinding.
[0099] The particle size of the layered diamond of the present invention is 20-2500 microns.
[0100] In the present invention, typical but non-limiting particle sizes of layered diamond are 20 microns, 40 microns, 60 microns, 80 microns, 100 microns, 120 microns, 140 microns, 160 microns, 180 microns, 200 microns, 220 microns, 240 microns, 260 microns, 280 microns, 300 microns, 350 microns, 400 microns, 450 microns, 500 microns, 550 microns, 600 microns, 650 microns, 700 microns, 750 microns, 800 microns, 850 microns, 900 microns, 950 microns, 1000 microns, 1500 microns, 2000 microns, and 2500 microns.
[0101] As a preferred embodiment of the present invention, the layered diamond is mainly prepared from the following raw materials in weight percentage: catalyst 30%-60%, graphite 30%-60%, No. 1 additive master powder 1%-10%, No. 2 additive master powder 1%-10%;
[0102] Wherein, the typical but non-limiting weight ratio of catalyst to graphite is: 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5. In the above preferred embodiment, the weight percentage of graphite in the No. 1 additive mother powder is 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%.
[0103] In the above preferred embodiment, the weight percentage of diamond powder in the No. 1 additive mother powder is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 30%, 40%, and 50%.
[0104] In the above preferred embodiment, the weight percentage of the metal aluminum powder in the additive mother powder No. 1 is 0.5%, 0.6%, 0.7%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0105] In the above preferred embodiment, the weight percentage of the metal titanium powder in the additive mother powder No. 1 is 0.5%, 0.6%, 0.7%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0106] In the above preferred embodiment, the weight percentage of amorphous boron powder in the No. 1 additive mother powder is 0.5%, 0.6%, 0.7%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0107] In the above preferred embodiment, the weight percentage of lithium nitride powder in the No. 2 additive mother powder is 0.5%, 0.6%, 0.7%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0108] In the above preferred embodiment, the weight percentage of carbon nitride powder in the No. 2 additive mother powder is 0.5%, 0.6%, 0.7%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0109] In a preferred embodiment of the present invention, the layered diamond is mainly prepared from the following raw materials in weight percentage: catalyst 30%-60%, graphite 30%-60%, No. 1 additive masterbatch 1%-10%, and No. 2 additive masterbatch 1%-10%.
[0110] As a more preferred embodiment of the present invention, the layered diamond is mainly prepared from the following raw materials in the following weight percentages: catalyst 38%-42%, graphite 55%-60%, No. 1 additive masterbatch 2%-3%, and No. 2 additive masterbatch 3%-5%.
[0111] Typical but non-limiting weight ratios of catalyst to graphite are: 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5.
[0112] By optimizing the ratio of each substance, the production of pellets can be made more uniform.
[0113] Another aspect of the present invention provides a method for preparing the above-mentioned polycrystalline diamond, which adopts a static pressing method, and places a sample raw material in a press device to pressurize and heat it for synthesis treatment to obtain the layered diamond.
[0114] As a preferred embodiment of the above-mentioned preparation method, the preparation method of the layered diamond is to mix the catalyst, graphite, additive master powder No. 1 and additive master powder No. 2 evenly and press them into columns, assemble them with accessories such as phyllite blocks and steel cups into synthetic blocks, place them in a six-sided top press, pressurize and heat the six-sided top press for synthesis treatment, the pressurization pressure of the six-sided top press is 70-85Mpa, and the temperature is 1350-1650℃.
[0115] Specifically, the method for preparing the layered diamond comprises the following steps:
[0116] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100 degrees in a nitrogen atmosphere and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0117] S2. Place the composite block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 5-7MPa in 0-1 second, then slowly increase the pressure to 50-55MPa in 90 seconds, and maintain the pressure for 500-550 seconds; when the pressure increases to 50-55MPa, start heating, and the temperature rises from room temperature to 1450-1650℃ for insulation:
[0118] S3, after the pressure maintenance at 50-55 MPa in step S2 is completed, the pressure is quickly increased to 60-65 MPa for pressure maintenance;
[0119] S4. After the pressure maintenance at 60-65 MPa in step S3 is completed, the temperature is reduced from 1450-1650° C. to 1350-1500° C. and maintained unchanged;
[0120] S5. After the temperature drops to 1350-1500°C, the pressure continues to increase to 75-85MPa and then maintain the pressure;
[0121] S6, after the pressure maintenance in step S5 is completed, the temperature is lowered, and when the temperature drops to room temperature, the pressure is released to synthesize a layered diamond synthetic rod.
[0122] Furthermore, in step S2, the pressure is first increased to 5-7 MPa after 1-2 seconds, and then increased to 50-55 MPa at a pressure rate of 0.3-0.8 MPa / s, and the pressure is maintained for 500-550 seconds; when the pressure is increased to 50-55 MPa, the temperature is increased from room temperature to 1450-1650° C. after 10-20 seconds and maintained;
[0123] Preferably, in step S3, after the pressure is maintained, the pressure is increased to 60-65 MPa for 80-95 seconds and maintained for 500-540 seconds;
[0124] Preferably, the pressure relief rate during pressure relief in step S6 is 0.5-1 MPa / s.
[0125] Preferably, the method for preparing the layered diamond comprises the following steps:
[0126] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100 degrees in a nitrogen atmosphere and assemble it into a synthetic block with pyrophyllite blocks, steel cups and other accessories.
[0127] S2. Place the composite block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 6MPa in 0-1 second, then slowly increase the pressure to 51-53MPa in 91 seconds, and maintain the pressure for 530-550 seconds; when the pressure increases to 51-53MPa, start heating, and the temperature rises from room temperature to 1450-1650℃ for insulation:
[0128] S3, after the pressure maintenance at 51-53 MPa in step S2 is completed, the pressure is quickly increased to 62-64 MPa for pressure maintenance;
[0129] S4. After the pressure maintenance at 62-64 MPa in step S3 is completed, the temperature is reduced from 1450-1600° C. to 1350-1500° C. and remains unchanged;
[0130] S5. After the temperature drops to 1350-1500°C, the pressure continues to increase to 76-80MPa and then maintains the pressure;
[0131] S6, after the pressure maintenance in step S5 is completed, the temperature is lowered, and when the temperature drops to room temperature, the pressure is released to synthesize a layered diamond synthetic rod.
[0132] Furthermore, the pressure relief rate during the pressure relief in step S6 is 0.5-0.6 MPa / s.
[0133] By optimizing the process of each step in the preparation method, the size of the prepared layered diamond particles can be made more uniform.
[0134] The pressures described in the above preparation methods are all the pressures applied by the six-sided top press. The model of the six-sided top press used in the present invention is 850, and the size of the synthetic column is 61.3mm*50.5mm.
[0135] The layered diamond prepared by the method provided by the present invention has an overall outer contour of a tetradecahedron and a layered internal structure, and is very suitable for cutting and grinding.
[0136] The present invention will be further described in detail below in conjunction with Examples 1-7 and Comparative Examples 1-4. Example 1
[0137] A layered diamond is mainly prepared from the following raw materials in percentage by weight: 40% catalyst, 50% graphite, 5% No. 1 additive master powder, and 5% No. 2 additive master powder;
[0138] The catalyst is a nickel-iron alloy powder, which includes 30% by mass of nickel and 70% by mass of iron.
[0139] The No. 1 additive masterbatch is mainly composed of the following raw materials in percentage by weight: 60% graphite, 15% diamond powder, 5% metal aluminum powder, 5% metal titanium powder, and 15% amorphous boron powder, and the sum of the weight percentages of the raw materials is 100%.
[0140] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 8.5 microns;
[0141] The quality purity of the metal aluminum powder in the No. 1 additive mother powder is 99.99%, and the D50 of the metal aluminum powder is 15 microns.
[0142] The mass purity of the metal titanium powder in the No. 1 additive masterbatch is 99.95%, and the D50 of the metal titanium powder is 12 microns.
[0143] The mass purity of the amorphous boron powder in the No. 1 additive masterbatch is 96%, and the D50 of the amorphous boron powder is 0.5 microns.
[0144] The No. 2 additive masterbatch is mainly composed of the following raw materials in percentage by weight: 40% graphite, 40% catalyst, 10% lithium nitride, and 10% carbon nitride.
[0145] The No. 2 additive mother powder is mainly prepared by the following raw materials and processes in weight percentage: 40% graphite, 40% catalyst, 5% lithium powder, and 15% urea. It is added into a rotary CVD deposition furnace and in-situ deposited under nitrogen protection. The deposition temperature of the in-situ deposition is 650 degrees Celsius to generate lithium nitride and carbon nitride.
[0146] The method for preparing the layered diamond comprises the following steps:
[0147] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100° C. in a nitrogen atmosphere and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0148] S2. Place the composite block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 6MPa in 0-1 second, then slowly increase the pressure to 52Mpa in 91 seconds, and maintain the pressure for 540 seconds; when the pressure increases to 52MPa, start heating, and keep the temperature from room temperature to 1450℃:
[0149] S3, after the pressure maintenance at 52 MPa in step S2 is completed, the pressure is quickly increased to 63 MPa for pressure maintenance;
[0150] S4. After the pressure maintenance at 63 MPa in step S3 is completed, the temperature is reduced from 1450° C. to 1400° C. and remains unchanged;
[0151] S5. After the temperature drops to 1400°C, the pressure continues to increase to 79MPa and then is maintained;
[0152] S6, after the pressure maintenance in step S5 is completed, the temperature is lowered, and when the temperature drops to room temperature, the pressure is released to synthesize a layered diamond synthetic rod.
[0153] The pressure relief rate during the pressure relief in step S6 is 0.5 MPa / s;
[0154] In step S2 of Example 1, the temperature is increased from room temperature to 1450° C., and the heating time is 36 minutes.
[0155] The layered diamond prepared by the method provided in Example 1 has an overall appearance of a tetradecahedron, a main particle size of 45 / 50, a main particle size content of 55%, Ti (cold impact toughness, three-grinding test center): 77.05, TTi (hot shock toughness, three-grinding test center): 74.1, Raman value (three-grinding test center): 5.03, and a layered internal structure, which is very suitable for diamond brazing and diamond wire saw beading.
[0156] Figure 1 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 1 of the present invention magnified 50 times. Figure 2 This is an electron microscope photograph of the layered polycrystalline diamond after the layered diamond obtained in Example 1 of the present invention was crushed. Figure 3 This is an electron microscope image of the cleavage surface of the layered diamond obtained in Example 1 after TI impact, magnified 5000 times.
[0157] Figure 4 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 1 of the present invention magnified 1000 times. Figure 5 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 1 of the present invention magnified 5000 times. Figure 6 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 1 of the present invention, magnified 10,000 times. Figure 7 Shown is the XRD pattern of the layered diamond obtained in Example 1 of the present invention. Fig.25 Shown is a photograph of the layered diamond with a primary particle size of 45 / 50 obtained in Example 1 of the present invention under an optical microscope.
[0158] As can be seen from the figure, the product obtained in Example 1 of the present invention is diamond and has a layered structure.
[0159] The layered diamond of this embodiment is a single crystal diamond with a layered structure; when the surface morphology of the layered diamond is observed in any direction, the layered diamond is a tetradecahedron or an octahedron; when the surface morphology of the layered diamond crushing surface is observed in any direction, the layered diamond crushing surface is a layered polycrystalline diamond structure.
[0160] The raw material ratios, parameters and operating steps not described in the following Examples 2-7 are the same as those in Example 1. Example 2
[0161] A layered diamond is mainly prepared from the following raw materials in percentage by weight: 40% catalyst, 50% graphite, 5% No. 1 additive master powder, and 5% No. 2 additive master powder;
[0162] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 6.5 microns;
[0163] The method for preparing the layered diamond comprises the following steps:
[0164] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100° C. in a nitrogen atmosphere and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0165] S2, placing the synthetic block into the high-pressure chamber of a six-sided top press, and preparing layered diamond using the same method as in Example 1;
[0166] In step S2 of Example 2, the temperature is raised from room temperature to 1450° C., and the heating time is 26 minutes;
[0167] Figure 8 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 2 of the present invention magnified 1000 times. Fig. 9 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 2 of the present invention magnified 5000 times. Fig.10 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 2 of the present invention, magnified 10,000 times. Fig.11 Shown is the XRD pattern of the layered diamond obtained in Example 2 of the present invention.
[0168] As can be seen from the figure, the product obtained in Example 2 of the present invention is diamond and has a layered structure.
[0169] The layered diamond prepared by the method provided in Example 2 has an overall shape of a tetradecahedron, a main particle size of 50 / 60, a main particle size content of 60%, Ti: 69.15, TTi: 65.2, Raman: 4.95, and a layered internal structure, which is very suitable for making phenolic resin bonded diamond tools, resin diamond grinding blocks, and resin diamond abrasive grains. Example 3
[0170] A layered diamond is mainly prepared from the following raw materials in percentage by weight: 45% catalyst, 45% graphite, 6% No. 1 additive master powder, and 4% No. 2 additive master powder;
[0171] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 6.0 microns;
[0172] The method for preparing the layered diamond comprises the following steps:
[0173] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100° C. in a nitrogen atmosphere and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0174] S2, placing the synthetic block into the high-pressure chamber of a six-sided top press, and preparing layered diamond using the same method as in Example 1;
[0175] In step S2 of Example 3, the temperature is raised from room temperature to 1450° C., and the heating time is 19 minutes;
[0176] Fig.12 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 3 of the present invention, magnified 1000 times. Fig.13 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 3 of the present invention, magnified 5000 times. Fig.14 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 3 of the present invention, magnified 10,000 times. Fig.15 Shown is the XRD pattern of the layered diamond obtained in Example 3 of the present invention.
[0177] As can be seen from the figure, the product obtained in Example 3 of the present invention is diamond and has a layered structure.
[0178] The layered diamond prepared by the method provided in Example 3 has an overall tetradecahedral shape, a primary particle size of 80 / 100, a primary particle content of 55%, Ti: 83.30, TTi: 79.5, Raman: 4.8, and a layered internal structure, which is very suitable for electroplating and brazing metal sintered diamond tools. Example 4
[0179] A layered diamond is mainly prepared from the following raw materials in percentage by weight: 45% catalyst, 45% graphite, 7% No. 1 additive master powder, and 3% No. 2 additive master powder;
[0180] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 5.0 microns;
[0181] The method for preparing the layered diamond comprises the following steps:
[0182] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100° C. in a nitrogen atmosphere and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0183] S2, placing the synthetic block into the high-pressure chamber of a six-sided top press, and preparing layered diamond using the same method as in Example 1;
[0184] In step S2 of Example 4, the temperature is raised from room temperature to 1450° C., and the heating time is 14 minutes;
[0185] The layered diamond prepared by the method provided in Example 4 has an overall tetradecahedral outline, a primary particle size of 100 / 120, a primary particle content of 51%, Ti: 77.3, TTi: 67.91, Raman: 5.06, and a layered internal structure, which is very suitable for electroplating, resin sintering, and ceramic sintering diamond tools.
[0186] Fig.16 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 4 of the present invention magnified 500 times. Fig.17 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 4 of the present invention magnified 2000 times. Fig.18 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 4 of the present invention, magnified 5000 times. Fig.19 Shown is the XRD pattern of the layered diamond obtained in Example 4 of the present invention.
[0187] As can be seen from the figure, the product obtained in Example 4 of the present invention is diamond and has a layered structure. Example 5
[0188] A layered diamond is mainly prepared from the following raw materials in percentage by weight: 50% catalyst, 40% graphite, 8% No. 1 additive master powder, and 2% No. 2 additive master powder;
[0189] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 4.0 microns;
[0190] The method for preparing the layered diamond comprises the following steps:
[0191] S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1100° C. in a nitrogen atmosphere and assemble it with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0192] S2, placing the synthetic block into the high-pressure chamber of a six-sided top press, and preparing layered diamond using the same method as in Example 1;
[0193] In step S2 of Example 5, the temperature is raised from room temperature to 1450° C., and the heating time is 12 minutes;
[0194] The layered diamond prepared by the method provided in Example 5 has an overall tetradecahedral shape, a main particle size of 230 / 270, a main particle content of 45%, Ti: 78.3, TTi: 74.4, Raman: 4.77, and a layered internal structure, which is very suitable for electroplating, resin sintering, and ceramic sintering diamond tools.
[0195] Fig. 20 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 5 of the present invention magnified 500 times. Fig.21 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 5 of the present invention magnified 2000 times. Fig. 22 Shown is an electron microscope photograph of the layered diamond particles obtained in Example 5 of the present invention, magnified 5000 times. Fig.23 Shown is the XRD pattern of the layered diamond obtained in Example 5 of the present invention.
[0196] As can be seen from the figure, the product obtained in Example 5 of the present invention is diamond and has a layered structure. Example 6
[0197] A layered diamond crushing material is prepared by using the layered diamond produced in Example 1 through a ball mill or a jet mill, and the particle sizes are: 80 / 100, 100 / 120, 120 / 140, 140 / 200, 200 / 230, 230 / 270, 270 / 325, 325 / 400, 400 / 500, 500 / 600; the crushing material has a layered nanostructure in cross section, and is very suitable for making resin sintered, ceramic sintered diamond tools, and resin polishing pads. Example 7
[0198] A layered diamond powder is prepared by ball milling or jet milling the layered diamond produced in Example 1, and the particle size model is: 30-40 (indicates D10 is 30 microns, D50 is 35 microns, D90 is 40 microns, and the following are similar), 20-30, 10-20, 8-16, 7-14, 5-10, 4-6, 3-6, 2-4,
[0199] 1-3, 0.5-1.5, 0-1; The diamond micro-section has a layered nanostructure, which is very suitable for diamond wire saws, resin polishing pads, and diamond polishing liquids. Example 8
[0200] The layered diamond powder of Example 7 is used, with a particle size of 1-3 and a D50 of 1.6 microns. A low-temperature ceramic binder is used, the layered diamond powder is used as an abrasive, and after mixing, titrating into balls, and sintering, an agglomerated abrasive with a secondary particle size of 35 microns is produced, model DCM1.6-601-35, such as Fig.24As shown. Polyol polishing liquid, agglomerated abrasive DCM1.6-601-35, abrasive solid content 2%. Used for thinning six-inch C-axis sapphire wafers. Test conditions are as follows:
[0201] Hard polishing pad pasting surface: 8mm copper plate plane, OD220mm
[0202] Hard polished mat pattern: Hexagonal
[0203] Polishing liquid flow rate: 32.5ml / min
[0204] Down / up speed: 75 / 70
[0205] Processing pressure: 150kg, about 265g / cm^2
[0206] Run 1: 15 minutes of operation, deceleration rate 3.36um / min,
[0207] Run 2: 10 minutes of operation, deceleration rate 4.01um / min,
[0208] Run 3: 10 minutes of operation, deceleration rate 3.87um / min,
[0209] Run 4: 10 minutes of operation, deceleration rate 3.78um / min,
[0210] Six-inch C-axis sapphire wafer thinning rate 3.75um / min,
[0211] Roughness Ra (arithmetic mean deviation of profile), 15 nm. Comparative Example 1
[0212] A single crystal diamond, mainly prepared from the following weight percentage of raw materials: catalyst 40%, graphite 55%, 1st additive mother powder 5%;
[0213] The No. 1 additive masterbatch is mainly prepared from the following raw materials in percentage by weight: 80% graphite and 20% diamond powder;
[0214] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 8.5 microns;
[0215] The method for preparing single crystal diamond comprises the following steps:
[0216] S1. Mix the catalyst, graphite and No. 1 additive master powder evenly and press them into a column. The column is sintered to 1100°C in a nitrogen atmosphere and assembled with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0217] S2, placing the synthetic block into the high-pressure chamber of a six-sided top press, and preparing single crystal diamond using the same method as in Example 1;
[0218] In step S2 of comparative example 1, the temperature was raised from room temperature to 1450° C., and the heating time was 45 minutes;
[0219] The single crystal diamond prepared by the method provided in Comparative Example 1 has an overall tetradecahedral shape, a main particle size of 40 / 45, a main particle content of 50%, Ti: 59.3, TTi: 51.3, Raman: 3.17, and is suitable for general-purpose diamond tools. Comparative Example 2
[0220] A single crystal diamond is mainly prepared from the following raw materials in percentage by weight: 45% catalyst, 50% graphite, and 5% No. 1 additive mother powder;
[0221] The No. 1 additive masterbatch is mainly prepared from the following raw materials in percentage by weight: 70% graphite and 30% diamond powder;
[0222] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 6.5 microns;
[0223] The method for preparing single crystal diamond comprises the following steps:
[0224] S1. Mix the catalyst, graphite and No. 1 additive master powder evenly and press them into a column. The column is sintered to 1100°C in a nitrogen atmosphere and assembled with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0225] S2, placing the synthetic block into the high-pressure chamber of a six-sided top press, and preparing single crystal diamond using the same method as in Example 1;
[0226] In step S2 of comparative example 2, the temperature was raised from room temperature to 1450° C., and the heating time was 19 minutes;
[0227] The single crystal diamond prepared by the method provided in Comparative Example 2 has an overall tetradecahedral shape, a main particle size of 70 / 80, a main particle content of 55%, Ti: 76.1, TTi: 73.3, Raman: 3.5, and is suitable for general-purpose diamond tools. Comparative Example 3
[0228] A single crystal diamond is mainly prepared from the following raw materials in percentage by weight: 40% catalyst, 52% graphite and 8% No. 1 additive mother powder.
[0229] The No. 1 additive masterbatch is mainly prepared from the following raw materials in percentage by weight: 65% graphite and 35% diamond powder;
[0230] The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 5 microns;
[0231] The method for preparing single crystal diamond comprises the following steps:
[0232] S1. Mix the catalyst, graphite and No. 1 additive master powder evenly and press them into a column. The column is sintered to 1100°C in a nitrogen atmosphere and assembled with pyrophyllite blocks, steel cups and other accessories into a synthetic block.
[0233] S2, placing the synthesized block into a high-pressure chamber of a six-sided top press, and preparing a single crystal diamond using the same method as in Example 1;
[0234] In step S2 of comparative example 3, the temperature was raised from room temperature to 1450° C., and the heating time was 13 minutes;
[0235] The single crystal diamond prepared by the method provided in Comparative Example 3 has an overall shape of a tetradecahedron, a primary particle size of 120 / 140, a primary particle content of 45%, Ti: 66.7, TTi: 61.9, Raman: 2.5, and is suitable for general-purpose diamond tools. Comparative Example 4
[0236] Polycrystalline diamond produced by Beijing Guoruisheng using the explosion method.
[0237] By using an electron microscope to observe and measure the polycrystalline diamonds produced by Beijing Guoruisheng using the explosion method, it can be concluded that the polycrystalline diamond grains produced by the explosion method have a particle size of 5-7 nanometers and a particle size of 0-9 microns. Comparative Example 5
[0238] The diamond powder of type II from Zhongnan Diamond is used, with a particle size of 1-3, D50 1.6 microns. Low-temperature ceramic binder is used, and the diamond powder is used as abrasive. After mixing, titration into balls, and sintering, agglomerated abrasive with a secondary particle size of 35 microns, model DS1.6-601-35, is produced. Polyol polishing liquid is used, agglomerated abrasive DS1.6-601-35-2, and the abrasive solid content is 2%. It is used for thinning six-inch C-axis sapphire wafers. The test conditions are as follows:
[0239] Hard polishing pad pasting surface: 8mm copper plate plane, OD220mm
[0240] Hard polished mat pattern: Hexagonal
[0241] Polishing liquid flow rate: 32.5ml / min
[0242] Down / up speed: 75 / 70
[0243] Processing pressure: 150kg, about 265g / cm^2
[0244] Run 1: 15 minutes of operation, deceleration rate 2.58um / min,
[0245] Run 2: 10 minutes of operation, deceleration rate 3.03um / min,
[0246] Run 3: 10 minutes of operation, deceleration rate 2.95um / min,
[0247] Run 4: 10 minutes of operation, deceleration rate 2.93um / min,
[0248] The thinning rate of six-inch C-axis sapphire wafer is 2.87um / min.
[0249] Roughness Ra (arithmetic mean deviation of profile), 16 nm.
[0250] The technical problem to be solved by the present invention is that single crystal diamond and polycrystalline diamond have few cutting edges, low grinding efficiency and short life. In Example 8, the agglomerated abrasive produced by the layered diamond micro-powder of the present invention is used for the thinning rate of 3.75um / min for six-inch C-axis sapphire wafers, and the roughness Ra (arithmetic mean deviation of the profile) is 15 nanometers. In Comparative Example 5, the agglomerated abrasive produced by the diamond micro-powder of Zhongnan Diamond Type II is used for the thinning rate of 2.87um / min for six-inch C-axis sapphire wafers, and the roughness Ra (arithmetic mean deviation of the profile) is 16 nanometers.
[0251] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. It is therefore intended that all such changes and modifications that fall within the scope of the present invention be included in the appended claims.
Claims
1. A layered diamond, characterized in that: It is a diamond having a layered structure; when the surface morphology of the layered diamond is observed in any direction, the layered diamond is a tetradecahedron; when the surface morphology of the broken surface of the layered diamond is observed in any direction, the broken surface of the layered diamond is a layered polycrystalline diamond structure; The layered diamond is mainly prepared from the following raw materials in percentage by weight: 30%-60% catalyst, 30%-60% graphite, 1%-10% No. 1 additive master powder, 1%-10% No. 2 additive master powder, and the sum of the weight percentages of the raw materials is 100%; The catalyst is a nickel-iron alloy powder, which includes 20-40% by mass of nickel and 60-80% by mass of iron; The No. 1 additive masterbatch is mainly composed of the following raw materials in percentage by weight: 50-90% graphite, 10%-50% diamond powder, 0.5%-15% metal aluminum powder, 0.5%-15% metal titanium powder, and 0.5%-15% amorphous boron powder, and the sum of the weight percentages of the raw materials is 100%; The No. 2 additive masterbatch is mainly composed of the following raw materials in percentage by weight: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium nitride, and 0.5%-15% carbon nitride.
2. The layered diamond according to claim 1, characterized in that The particle size of the layered diamond is between 20 and 2500 microns.
3. The layered diamond according to claim 1 or 2, characterized in that: The diamond powder in the No. 1 additive masterbatch is produced from Type II or higher quality diamonds, and the D50 of the diamond powder is 4-9.5 microns; And / or, the diamond powder in the No. 1 additive mother powder is a layered diamond powder produced from layered diamond with a Ti value greater than 70 as a raw material, and the diamond powder D50 is one of 4-5 microns, 5-6 microns, 6-7 microns, 7-8 microns, and 8-9 microns; And / or, the purity of the metal aluminum powder in the No. 1 additive masterbatch is greater than or equal to 99.99%; and / or, the metal aluminum powder in the No. 1 additive master powder has a D50 of 10-20 microns; And / or, the purity of the metal titanium powder in the No. 1 additive master powder is greater than 99.9%, and the D50 of the metal titanium powder is 10-20 microns; And / or, the mass purity of the amorphous boron powder in the No. 1 additive master powder is greater than 99%, and the D50 of the amorphous boron powder is 0.1-10 microns.
4. The layered diamond according to claim 3, characterized in that The No. 2 additive masterbatch is mainly prepared by the following raw materials and processes in weight percentage: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, 1%-30% urea, added into a rotary CVD deposition furnace, in-situ deposited under nitrogen protection to generate lithium nitride and carbon nitride; Alternatively, the No. 2 additive master powder is mainly prepared from the following raw materials in percentage by weight: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, 1%-30% urea, added into a rotary CVD deposition furnace, and in-situ deposited under the protection of nitrogen and argon to generate lithium nitride and carbon nitride; Alternatively, the No. 2 additive masterbatch is mainly prepared from the following raw materials in the following weight percentages: 30-50% graphite, 30-50% catalyst, 0.5%-15% lithium powder, and 1%-30% urea, which is added into a rotary CVD deposition furnace and deposited in situ under the protection of nitrogen and hydrogen to generate lithium nitride and carbon nitride.
5. A method for preparing a layered diamond according to any one of claims 1 to 4, characterized in that: The static pressure method is adopted to place the raw material in a press device and pressurize and heat it for synthesis treatment to obtain the layered diamond.
6. The method for preparing layered diamond according to claim 5, characterized in that: The preparation method of layered diamond comprises the following steps: mixing catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder uniformly and pressing them into columns, assembling them with phyllite blocks and steel cups into synthetic blocks, placing them in a six-sided top press or a two-sided top press, and pressurizing and heating the six-sided top press or the two-sided top press for synthetic treatment.
7. The method for preparing layered diamond according to claim 5 or 6, characterized in that: The method for preparing the layered diamond comprises the following steps: S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1000° C.-1200° C. in a nitrogen atmosphere and assemble it with a pyrophyllite block and a steel cup into a synthetic block. S2. Place the composite block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 5-7Mpa in 0-3 seconds, then slowly pressurize to 50-55Mpa in 80-100 seconds, and maintain the pressure for 450-600 seconds; when the pressure increases to 50-55MPa, start heating and temperature rise from room temperature to 1450-1650℃, and keep the temperature; S3. After the pressure maintenance at 50-55 MPa in step S2 is completed, the pressure is quickly increased to 60-65 MPa for pressure maintenance for 500 seconds to 650 seconds; S4. After the pressure maintenance at 60-65 MPa in step S3 is completed, the temperature is reduced from 1450-1650° C. to 1350-1500° C. and maintained unchanged; S5. After the temperature drops to 1350-1500°C, the pressure is further increased to 75-85MPa and maintained for 800-1200 seconds. S6, after the pressure maintenance in step S5 is completed, the temperature begins to drop, and the pressure is released when the temperature drops to room temperature, that is, a layered diamond synthetic rod is synthesized; the layered diamond synthetic rod is first mechanically crushed and chemically electrolyzed to remove the catalyst metal, and the excess graphite is removed by a shaking table, and then pickled, sieved, and selected to obtain coarse and fine particle layered diamond.
8. The method for preparing layered diamond according to claim 7, characterized in that: In step S2, the pressure is first increased to 5-7 MPa after 1-2 seconds, and then increased to 50-55 MPa at a pressure rate of 0.3-0.8 MPa / s, and the pressure is maintained for 500-550 seconds; when the pressure is increased to 50-55 MPa, heating is started, and the temperature is increased from room temperature to 1450-1650° C. after 10-20 seconds, and the temperature is maintained; And / or, in step S3, after the pressure is maintained at 50-55 MPa, the pressure is rapidly increased to 60-65 MPa over 80-95 seconds, and the pressure is maintained for 500-540 seconds; And / or, the pressure relief rate during pressure relief in step S6 is 0.5-1 MPa / s.
9. The method for preparing layered diamond according to claim 7, characterized in that: The method for preparing the layered diamond comprises the following steps: S1. Mix the catalyst, graphite, No. 1 additive master powder and No. 2 additive master powder evenly and press them into a column. Sinter the column to 1000° C.-1200° C. in a nitrogen atmosphere and assemble it with a pyrophyllite block and a steel cup into a synthetic block. S2. Place the composite block into the high-pressure chamber of the six-sided top press, first quickly pressurize to 6MPa in 0-1 second, then slowly increase the pressure to 51-53Mpa in 90 seconds, and maintain the pressure for 530-550 seconds; when the pressure increases to 51-53MPa, start heating and temperature rise from room temperature to 1450-1650℃, and keep the temperature; S3, after the pressure maintenance at 51-53 MPa in step S2 is completed, the pressure is quickly increased to 62-64 MPa for pressure maintenance; S4. After the pressure maintenance at 62-64 MPa in step S3 is completed, the temperature is reduced from 1450-1650° C. to 1350-1500° C. and maintained unchanged; S5. After the temperature drops to 1350-1500°C, continue to increase the pressure to 76-80MPa and maintain the pressure; S6, after the pressure maintenance in step S5 is completed, the temperature is lowered, and when the temperature drops to room temperature, the pressure is released to synthesize a layered diamond synthetic rod.
Citation Information
Patent Citations
Polycrystalline diamond, tool and polycrystalline diamond synthetic process
CN107670588A
A method of producing a polycrystalline diamond aggregate
GB1300650A